Project managers in construction: an analysis of skills, satisfaction and quality of life - Silveira, Maitê Rocha; Silva, Vanderléia de Souza da; Poker Junior, Johan Hendrik (Brazilian Journal of Production Engineering, 2022)
The importance of project management has had a greater focus in the Information Age, due to the volatility and high level of changes, which demand better planning and effectiveness from organizations. Civil construction is situated in this perspective. This industry is different from the others in terms of the development of its products and lack of advances in technology. Project managers, as in most industries, play an important role in the functional dynamics of organizations in civil construction. The varied demands of this environment require from them certain competencies regarding decision making and the resolution of productive impasses. In this context, the aim of this study is to identify the competencies required of project managers in civil construction, and the factors that influence their job satisfaction and quality of life. To this end, an online questionnaire was applied, based on previous bibliographies. The data collected was analyzed using quantitative and qualitative methods. The main practical contribution of this work is to present empirical evidence that the competencies perceived as valuable for the project manager focused on the national construction industry are planning and organization, effective communication, and change management. These results contribute to the topic by discussing in depth the specific area of civil construction. As for satisfaction and quality of life at work, it was found that despite the high levels of stress analyzed, most presented high levels of satisfaction related to the position held and the activities performed during the workday.